أحمد بن نصر الداودي (402هـ) إنتاجه العلمي وإسهاماته المعرفية - اليمان عبد الجبار (University of Eloued جامعة الوادي, 2024)
هذا المقال المعنون ب: "أحمد بن نصر الداودي إنتاجه العلمي وإسهاماته المعرفية" يبين لنا مدى مكانة علماء الجزائر في الساحة العلمية ومساهمتهم المعرفية في شتى العلوم؛ وخاصة الشرعية منها، ومن بين هؤلاء العلماء؛ العالم الموسوعي أحمد بن نصر الداودي (402ه)، الذي يعتبر أول من شرح صحيح البخاري؛ إضافة إلى تآليفه المفيدة في التفسير والحديث والفقه والأصول... وغيرها، فأردت من خلال هذا المقال إبراز الإنتاج العلمي المنوّع للإمام الداودي، فطرحت الإشكال التالي: إلى أيّ مدى ساهم الإمام الداودي في المجال المعرفي من خلال إنتاجاته العلمية المنوعة؟ وللإجابة على هذا الإشكال انتهجت خطة من مقدمة ومبحثين وخاتمة. This article, entitled: "Ahmed Ibn Nasr al-Daoudi, his Scientific Production and Knowledge Contributions," shows us the considered status of Algerian scholars in many various fields of science and knowledge contribution especially the religious ones. Among these scholars we notice The encyclopedic scholar Ahmed bin Nasr Al-Dawoodi (402 AH), who is considered the first who explains Sahih Al-Bukhari, in addition to his useful compositions in interpretation, hadith, jurisprudence, origins and so on. I wanted, through this article, to highlight the diversified scientific production of Imam Al-Dawoodi, so I presented the following question : " To what extent did Imam Al-Dawoodi contribute in the field of knowledge through his various scientific productions"? . In order to answer this statement, I followed a plan of ; introduction, two chapters and a conclusion
Keywords: علماء الجزائر; الإمام الداودي; الإنتاج العلمي; المساهمة المعرفية; Algerian scholars; Imam daoudi; Scientific production; Knowledge contribution